Um estudo sobre a composi????o da d??vida p??blica utilizando a modelagem DSGE - Moraes, Adriano Sodr?? de (2016)
This dissertation applies a Dynamic Stochastic General Equilibrium ??? DSGE model to the Brazilian economy, doing simulations on the main macroeconomic variables of the economy. The model of Divino and Silva Junior (2014) was modified to include bonds linked to the economy??s basic interest rate and used to analyze the dynamics of the economy under alternative scenarios for the fiscal policy. It is performed a welfare analysis exploring the relationship between debt composition and the monetary policy willingness to fight inflation versus stabilize the output gap. The results suggest that a higher degree of public debt indexation should increase the welfare of the economy.